The Amino Acid-Mediated TOR Pathway Regulates Reproductive Potential and Population Growth in Cyrtorhinus lividipennis Reuter (Hemiptera: Miridae) - Zhu, Haowen; Zheng, Sui; Xu, Jinming; Wu, Qing; Song, Qisheng; Ge, Linquan (Frontiers in Physiology, 2020)
The predatory mirid bug, Cyrtorhinus lividipennis Reuter, feeds on brown planthopper (BPH) eggs that are deposited on rice and gramineous plants surrounding rice fields. The development and reproduction of C. lividipennis is inhibited by feeding on BPH eggs from gramineous species, and the underlining regulatory mechanism for this phenomenon is unclear. In the present study, HPLC-MS/MS analysis revealed that the concentrations of six amino acids (AAs: Ala, Arg, Ser, Lys, Thr and Pro) were significantly higher in rice than in five gramineous species. When C. lividipennis fed on gramineous plants with BPH eggs, expression of several genes in the target of rapamycin (TOR) pathway (Rheb, TOR, and S6K) were significantly lower than that in the insects fed on rice plants with BPH eggs. Treatment of C. lividipennis females with rapamycin, dsRheb, dsTOR or dsS6K caused a decrease in Rheb, TOR, and S6K expression, and these effects were partially rescued by the JH analogue, methoprene. Dietary dsTOR-treatment significantly influenced a number of physiological parameters and resulted in impaired predatory capacity, fecundity and population growth. This study indicates that these six amino acids play an important role in mediated-TOR pathway, which in turn regulates Vg synthesis, reproduction and population growth in C. lividipennis.